Rural education in boyacá, strengths and weaknesses from teachers’ viewpoint - Herrera Torres, Lucía; Buitrago Bonilla, Rafael Enrique (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This work makes explicit some strengths and weaknesses of the rural area in relation to the urban one from teachers’ viewpoint about some aspects of the educational context and the institutional needs in the provinces of Centro, Tundama and Sugamuxi (Boyacá). The final sample consisted of 434 teachers. A questionnaire on the current educational situation in rural and urban schools of Boyacá was used for data collection. The content validity of the questionnaire was analyzed through the Expert Judgment Technique. As for the internal consistency, Cronbach alpha was 0.79. The main results revealed significant differences in the relationship between teachers and students -better in the rural area- as well as in the needs -rural institutions had higher requirements.